PERAN PUSAT INFORMASI KONSELING REMAJA (PIK-R) DALAM PENCEGAHAN PENYALAHGUNAAN NARKOTIKA MELALUI PENYULUHAN DI KECAMATAN SAMARINDA UTARA - Meri Meri (Magister Administrasi Publik FISIP Universitas Mulawarman, 2020)
This study aimed to analyze the role of the Adolescent Counseling Information Center in Narcotics Abuse Prevention through Counseling in North Samarinda District. The type of this research was a qualitative descriptive study. The data collection technique of this research used interviews, documentations, and literature methods. The data analysis used was an interactive data analysis model. The results of this research showed that the Adolescent Counseling Information Center has done the direct counseling through presentations at junior high schools, high schools and the private school in North Samarinda District, from the counseling that has been done, there were 8 schools from 42 schools that were given counseling at once in each school with the limited number of students between 40-60 students who had free time. Keywords: Counseling, Adolescents, Prevention, Narcotics Abuse, Drug Counseling